Meeting God at every turn A personal family story - Marshall, Catherine (Lincoln, VA Chosen Books Pub. Co., 1980)
This is a true story of how God has met me and is still meeting me at every turn. I know that He is the answer to every cry of your heart.
Keywords: Marshall, Catherine, -- 1914-1983. Christian biography -- United States. Marshall, Catherine, -- 1914-1983